A Comparative Study on Na2Fe0.6Mn0.4PO4F/C Cathode Materials Synthesized With Various Carbon Sources for Na-ion Batteries - Tang, Shibao; Zhang, Xiaoping; Sui, Yulei; Wang, Bingjue; Li, Jiangpeng; Wu, Ling (Frontiers in Chemistry, 2021)
Na2Fe0.6Mn0.4PO4F/C composite materials are synthesized with various carbon sources via a simple spray-drying method in this study, and the effect of carbon sources on structure, morphology and electrochemical properties of Na2Fe0.6Mn0.4PO4F/C materials are investigated in detail. XRD and SEM results indicate that the reduction ability of carbon sources has a key impact on the structure and morphology of Na2Fe0.6Mn0.4PO4F/C composite materials. Among these Na2Fe0.6Mn0.4PO4F/C materials, the sample prepared with ascorbic acid presents uniform hollow spherical architecture. Electrochemical analysis demonstrates that the Na2Fe0.6Mn0.4PO4F/C sample prepared with ascorbic acid has optimal electrochemical performance. The sample shows high discharge capacities of 95.1 and 48.1 mAh g-1 at 0.05C and 1C rates, respectively, and it exhibits an improved cycle stability (91.7% retention after 100 cycles at 0.5C), which are superior to Na2Fe0.6Mn0.4PO4F/C materials prepared with other carbon sources. This study demonstrates that the reduction ability of carbon sources significantly influences the electrochemical properties of fluorophosphate/C composite materials. Besides, this work also provides a promising strategy to obtain high performance cathode materials for sodium-ion batteries.